1992
DOI: 10.1017/s0003356100036953
|View full text |Cite
|
Sign up to set email alerts
|

A note on the ease of handling and flight distance of Bos indicus, Bos taurus and their crossbreds

Abstract: Ease of handling (time to enter and exit scales and dip, and temperament scores) and flight distance were studied in Bos indicus and Bos taurus cattle and their crossbreds. At one research station (LS), 20 cows and 20 female calves, each of N'dama and West African Shorthorn (WASH) cattle were used. At another research station (BRS), 15 cows each of N'dama, Holstein and their crossbreds (NH) were used for the study. In addition a further 20 cows and 20 female calves of the N'dama breed were studied at BRS for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 4 publications
0
8
0
3
Order By: Relevance
“…Some others studies have revealed distinct reactions between genotypes, reporting for Bos indicus breeds or crossbreds greater agitation compared with Bos taurus (Grandin & Deesing, 1998;Barbosa-Silveira et al, 2006;Barbosa-Silveira et al, 2008a, b). However, Kabuga & Appiah (1992) did not verify differences of handling ease between Bos taurus and Bos indicus crossbred steers, suggesting that it was more influenced by raising conditions and previous management.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Some others studies have revealed distinct reactions between genotypes, reporting for Bos indicus breeds or crossbreds greater agitation compared with Bos taurus (Grandin & Deesing, 1998;Barbosa-Silveira et al, 2006;Barbosa-Silveira et al, 2008a, b). However, Kabuga & Appiah (1992) did not verify differences of handling ease between Bos taurus and Bos indicus crossbred steers, suggesting that it was more influenced by raising conditions and previous management.…”
Section: Discussionmentioning
confidence: 71%
“…Highly agitated or flighty animals yield tougher meat (Voisinet et al, 1997b;King et al, 2006;Kadel et al, 2006) and present higher losses of meat due to bruising (Fordyce et al, 1988b). However, Kabuga & Appiah (1992) and Barbosa-Silveira et al (2008a) did not verify differences for weight gain between genetic groups of Bos taurus and Bos indicus crossbred steers. These authors suggested that management ease was more influenced by raising conditions and previous management experience than by genetic basis.…”
Section: Introductionmentioning
confidence: 94%
“…Entretanto, Sato (1981) identificou que o temperamento do animal não, necessariamente, melhora com a idade e que a melhora está mais associada ao manejo ao qual ele é criado. Segundo alguns autores o efeito do manejo sobre o temperamento bovino é função da experiência passada vivida pelo animal naquele manejo, logo se o animal não sofrer seu temperamento melhora (Sato, 1981;Kabuga & Appiah, 1992;Becker, 1994;Andrade et al, 2001;Uetake et al, 2002;Petherick et al, 2002;Neindre et al, 1996;Beckman et al, 2007). Maffei (2009) não encontrou diferença na reatividade de grupos de contemporâneos de animais da raça Nelore com diferença máxima de idade de três (3) meses.…”
Section: Idade Do Animal E Manejounclassified
“…Kabuga and Appiah (1992) suggested that the ease of cattle handling is influenced a lot more by the raising conditions and experience of the farmer than it is by genetics, after studying Bos indicus that were crossbred with Bos taurus steers. The researchers did not find any differences in temperament between the genetic groups.…”
Section: Introductionmentioning
confidence: 99%